Human Epidermal Growth Factor Receptor-2 Overexpression in Epithelial Ovarian Cancers - Zaib, Laila (International Journal of Pathology, 2023)
Introduction: HER2 (human epidermal growth factor receptor-2) proto-oncogene encodes a protein belonging to the EGFR tyrosine kinase receptor family. Overexpression of HER2 initiates intracellular signaling pathways involved in cell proliferation, differentiation, migration, and apoptosis. Objectives: To determine Her2 overexpression in epithelial ovarian cancers. Materials & Methods; This Descriptive, cross-sectional study was carried out in the Department of Pathology, in Combined Military Hospital, Quetta from July 2017 to January 2018. A total of 95 biopsies and resected specimens of all patients with epithelial ovarian cancer of age 25-65 years were included. Patients with non-epithelial ovarian malignancies, malignancies in other organ systems, recurrent ovarian tumors, and radiotherapy given cases were excluded. After gross examination, the tissues were processed in an automatic tissue processor, and blocks were prepared, followed by cutting, slide preparation, and staining with hematoxylin and eosin (H&E) stain. Immunohistochemistry was used for overexpression (positive/negative) of Her2/neu. Results: Mean age was 47.01 ± 10.74 years. The mean duration of the disease was 5.81 ± 2.01 months. The frequency of Her2 overexpression in epithelial ovarian cancer was seen in 23 (24.21%) cases. Conclusion: It was concluded in this study that there was a high frequency of Her2 overexpression in epithelial ovarian cancers.